Strategi Literasi Melalui Program Membaca Nyaring Simba: Upaya Meningkatkan Minat Baca Siswa SD Muhammadiyah Kompleks Gresik - Eka Mei Tasari; Erna Yayuk; Kiki Hajriyani; Muhammad Andy Purnama (LPPM Institut Pendidikan Nusantara Global, 2026)
Low reading literacy and sociological-digital shifts post-COVID-19 pandemic have triggered learning loss and a decline in reading interest among elementary school students, which is further exacerbated by conventional literacy programs that remain teacher-centered. This study aims to deeply describe the planning, implementation, evaluation, impacts, and contextual constraints of the SIMBA (Simak dan Baca / Listen and Read) program at SD Muhammadiyah Kompleks Gresik as a literacy strategy to enhance elementary school students' reading interest. This study employed a descriptive qualitative approach with a case study design. Participants were selected through purposive sampling and consisted of one principal, six classroom teachers, two members of the school literacy team, and five students, selected based on their involvement in the school literacy program. Data were gathered through observation, structured interviews, and documentation studies, then analyzed using the Miles, Huberman, and Saldaña interactive model consisting of data reduction, data display, and conclusion drawing, with validity ensured through source and technique triangulation. The results indicate that the SIMBA program, which integrates read-aloud strategies with digital media and face-to-face activities, indicates positive changes in students’ reading interest. This is evidenced by increased student enthusiasm in reading activities, higher frequency of library visits, and active student involvement as read-aloud performers. Furthermore, the program contributes to the development of a collaborative school literacy culture supported by strong leadership and community engagement. Therefore, the SIMBA program can serve as an innovative, adaptive, and sustainable literacy strategy to improve elementary students' reading interest, particularly in addressing the challenges of the digital era.